2016
DOI: 10.2217/epi-2016-0063
|View full text |Cite
|
Sign up to set email alerts
|

Scan_Tcga Tools for Integrated Epigenomic and Transcriptomic Analysis of Tumor Subgroups

Abstract: Aim:The Cancer Genome Atlas contains multiple levels of genomic data (mutation, gene expression, DNA methylation, copy number variation) for 33 cancer types for almost 11,000 patients. However, a dearth of appropriate software tools makes it difficult for bench scientists to use these data effectively. Materials & methods: Here, we present a suite of flexible, fast and command line-based scripts that will allow retrieval and analysis of DNA methylation (tool: scan_tcga_methylation.awk), mRNA (tool: scan_tcga_m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…These RRBS methylation patterns were remarkably similar within a group (inducible or constitutive), which we hypothesize is the result of a unified mechanism leading to hypomethylation of particular genomic regions across all the PD-L1 constitutively expressing cell lines. Consistent with previously reported data, we found the CD274 promoter was unmethylated ( Chatterjee et al., 2016 ), with no evidence of differential methylation occurring in the core promoter itself, which argues against methylation of the CD274 promoter being involved in constitutive PD-L1 expression. In addition, blocking IFN-γ or interferon type I or type II with antibodies did not inhibit constitutive PD-L1 expression but (surprisingly) consistently enhanced constitutive PD-L1 expression.…”
Section: Discussionsupporting
confidence: 92%
“…These RRBS methylation patterns were remarkably similar within a group (inducible or constitutive), which we hypothesize is the result of a unified mechanism leading to hypomethylation of particular genomic regions across all the PD-L1 constitutively expressing cell lines. Consistent with previously reported data, we found the CD274 promoter was unmethylated ( Chatterjee et al., 2016 ), with no evidence of differential methylation occurring in the core promoter itself, which argues against methylation of the CD274 promoter being involved in constitutive PD-L1 expression. In addition, blocking IFN-γ or interferon type I or type II with antibodies did not inhibit constitutive PD-L1 expression but (surprisingly) consistently enhanced constitutive PD-L1 expression.…”
Section: Discussionsupporting
confidence: 92%
“…For the majority of sites the data were not distributed normally, and therefore a Mann-Whitney U test was also performed. These analyses were performed using the scan_tcga set of tools [49]. …”
Section: Methodsmentioning
confidence: 99%
“…It was questioned whether low PD-L1 expression could be attributed to methylation of the promoter region encoding PD-L1, as prior studies in lung carcinoma have linked resistance to anti-PD1 antibody treatment with DNA methylation at the promoter region [22]. Previous analysis of the Skin Cutaneous Melanoma (SKCM) TCGA data revealed two CpG sites in the proximal promoter region encoding PD-L1, which were not methylated [23,24]. These observations suggested that a distal enhancer similar to an enhancer previously described might be involved in the epigenetic regulation of PD-L1 [25].…”
Section: Dna Methylation Status In Melanoma Tumorsmentioning
confidence: 99%